Implementing a contextual pedagogical approach in junior high school science education - Alfian Erprabowo; Eko Edi Sujarwo (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: Science education at the junior high school level often faces challenges in enhancing student engagement and understanding of scientific concepts. A contextual pedagogical approach, which connects the subject matter to students’ everyday experiences, is believed to improve the effectiveness of learning.Aim: This study aims to implement a contextual pedagogical approach in science education and examine its impact on student learning activities, academic achievement, and student responses in a junior high school setting.Method: This research employed a classroom action research method conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were eighth-grade students at a junior high school. Data were collected through activity observation sheets, learning outcome tests, and student response questionnaires. The data were analyzed using descriptive quantitative methods.Results: The findings indicated a significant increase in student learning activity, from an average of 66.2% in the first cycle to 85% in the second cycle. The average post-test score improved from 73.2 to 80.2, with the mastery level increasing from 46.7% to 83.3%. Student responses were also positive, with 90% reporting that the lessons were more engaging and 86% feeling more confident in group discussions.Conclusion: The contextual pedagogical approach proved effective in enhancing student engagement and comprehension in science learning. It is recommended that teachers consistently implement this approach to foster meaningful and relevant learning experiences for students.